Travels from the Periphery and Back: Latin American Painters in Paris at the End of the Nineteenth Century. (2nd October 2019) - Pravdenko, Inna
Abstract : In the nineteenth century, aspiring artists from many parts of the world were going to Europe in search of artistic perfection. In Paris, like in the principal European capitals of the time, there existed wide networks of migrating artists, international exhibitions, and travelling artworks. This circulation of people and goods shaped the global art system and formed its underlying structure. Even if Latin American painters contributed to these networks and expanded them from Europe to the New World, their role in the establishment of the modernist canon is not yet fully recognized. Because of the reductive art historical narrative and the paucity of archival records, many names of Latin American artists have disappeared from art historical accounts, and many works of art have been held in isolation in the store rooms of peripheral museums, or disappeared into private collections. The significant absence of these painters, often explained in terms of their backwardness and derivative style, is here determined by the structural inequality between the artistic center for which they longed and the periphery from which they came. This article explores the trajectories of Latin American painters in Paris who participated in the Salons of the Société Nationale des Beaux-arts from 1890 to 1899, and revisits their position in the modern canon.